Reconstructing Agricultural Self-Sufficiency at Chunchucmil, Yucatan, Mexico - Dahlin, B. H.; Beach, T.; Luzzadder-Beach, S.; Hixson, D.; Hudson, S.; Mangnoni, A.; Mansell, E.; D. E. Mazeau (Ancient Mesoamerica, 2005)
The Pakbeh Regional Economy Program is studying the vexing questions of economic life among the ancient Maya in northwestern Yucatan, Mexico. The region constitutes an ideal laboratory in which to investigate these questions, as it has very limited agricultural potential and fewer options for intensification than are found in the southern and central lowlands, yet many times more people lived here during the Classic period than can eke out a living today, and it has abundant evidence of market trade. Because crop yields in outfields are very low, and known intensification techniques are possibly incapable of sufficient yield enhancement, we anticipated that it would be an easy task to demonstrate that this population was dependent on imports of food and other necessities of life from beyond the region and therefore had a complex exchange economy. Twelve years later, we report on how wrong we were. We are still struggling with an evaluation of agricultural insufficiency. We explore the many and varied lines of evidence we have pursued and the confounding factors inherent in them, including problems with reconstructing ancient population size, equating contemporary and historical crop yields and farming practices, as well as ancient with modern environmental conditions, and hypothesizing potential forms of agricultural intensification, including intensive fertilization and other yield enhancement techniques, and reliance on alternative crops. The best that we can say at this juncture is that using contemporary production and consumption standards, the most conservative population estimates, and the most liberal estimates of available land in the surrounding region, we can conclude only that regional agricultural self-sufficiency remains unlikely but not proved. What initially seemed like an archaeological “no-brainer” has required us to delve into the realm of archaeological epistemology that we would like to share with our colleagues.
Keywords: agricultural insufficiency; archaeological epistemology; Maya; Mexico